PENERAPAN MODEL PEMBELAJARAN COOPERATIVE LEARNING MEDIA INDEX CARD MATCH DALAM MENINGKATKAN KEATIFAN DAN HASIL BELAJAR SEJARAH SISWA KELAS X MIA 1 SMA NEGERI 1 SALEM KABUPATEN BREBES TAHUN AJARAN 2014/2015 - Munggara, Dudi Ramdhani (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2015)
Dudi Ramdhani Munggara. THE APPLICATION OF LEARNING MODEL OF COOPERATIVE LEARNING WITH INDEX CARD MATCH MEDIA IN INCREASING STUDENTS' ACTIVENESS AND LEARNING OUTCOMES IN HISTORY SUBJECT OF CLASS X MIA 1 SMA NEGERI 1 BREBES SALEM IN THE ACADEMIC YEAR OF 2014/2015. Thesis. Faculty of Education and Teacher Training. Sebelas Maret University Surakarta. July 2015.The purpose of this research is to enhance the students? activeness and learning outcomes of students in class X MIA 1 SMA Negeri 1 Salem Brebes by applying the teaching model of cooperative learning with index card match media in history subject.This research is a classroom action research (CAR). The research was conducted in two cycles, with each cycle consisting of a plan, action, observation, and reflection. The subjects were 38 students of class X MIA 1 SMA Negeri 1 Salem. Source of data was derived from the teacher, the students and the learning process. Data collection techniques were implemented by conducting tests, observations, interviews, documentation, and questionnaires. Testing the data validity was by using triangulation techniques. Data analysis was conducted by using comparative descriptive analysis techniques. The research model used was the spiral model (Planning, Acting, Observing and Reflecting).The results showed that the teacher could be categorized as be able to teach well in the learning process, so that the learning process ran well. The ability of teachers to teach in pre-cycle was 62.5% which increased to 79.5% in the first cycle and 85.71% in the second cycle. The implementation of teaching model of cooperative with index card match media could enhance the students? activeness and learning outcomes of studying history subject of class X MIA 1 in pre-cycle to the first cycle and from cycle I to cycle II. The students? activeness in pre-cycle was 63.15% which increased to 79.27% in the first cycle and 82.31% in the second cycle. The completeness of students? learning outcomes in pre-cycle was 65.79% which increased to 73.68% in the first cycle and successfully developed to 81.37 in the second cycle.Based on the results of research and discussion, it can be drawn the conclusion that the teaching model of cooperative learning with index card match media enhance the students? activeness and learning outcomes of class X MIA 1 SMA Negeri 1 Salem Brebes.